2012
DOI: 10.1002/adem.201200192
|View full text |Cite
|
Sign up to set email alerts
|

Paper‐Derived Bioactive Glass Tape

Abstract: Porous bioactive glass (BaG) structures were manufactured applying novel preceramic paper process. Preceramic papers were produced for aqueous suspensions loaded with different contents of pulp fiber and BaG filler. Pressure loading was applied in order to increase the packing density in the paper sheets. The paper sheets were sintered at 630 °C for 1 h. The porous glass–ceramic specimens were characterized for density, porosity, composition, microstructure, and mechanical properties. A pronounced volumetric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…As for the pulp fiber composition, the shorter, non‐refined hardwood pulp fibers made‐up a portion 60 vol% of the total pulp fiber content and the rest of the longer softwood pulp fibers. In previous studies on preceramic papers, the shorter pulp fibers were indicated to have an average diameter of 15 µm and an average fiber length of 657 µm, while the longer pulp fibers were indicated to have an average diameter of 22 µm and an average fiber length of 1665 µm. To obtain more precise values for the pulp fiber lengths and pulp fiber diameters, the pulp fiber dimensions were measured by the optical QIPIC/MIXCELL measuring system, carried out by the company Sympatec GmbH (Clausthal/Zellerfeld, Germany).…”
Section: Design and Manufacturing Of Highly Filled Papersmentioning
confidence: 98%
See 4 more Smart Citations
“…As for the pulp fiber composition, the shorter, non‐refined hardwood pulp fibers made‐up a portion 60 vol% of the total pulp fiber content and the rest of the longer softwood pulp fibers. In previous studies on preceramic papers, the shorter pulp fibers were indicated to have an average diameter of 15 µm and an average fiber length of 657 µm, while the longer pulp fibers were indicated to have an average diameter of 22 µm and an average fiber length of 1665 µm. To obtain more precise values for the pulp fiber lengths and pulp fiber diameters, the pulp fiber dimensions were measured by the optical QIPIC/MIXCELL measuring system, carried out by the company Sympatec GmbH (Clausthal/Zellerfeld, Germany).…”
Section: Design and Manufacturing Of Highly Filled Papersmentioning
confidence: 98%
“…For highly filled papers, particulate or fibrous fillers are expected to accumulate at positions surrounding the pulp fibers and within voids of the pulp fiber network. When heat‐treating highly filled papers, the porosity of paper‐derived ceramics, ceramic‐ and metal‐based composites is mainly determined by the intricate structure of the pulp fiber network . Spaces in between individual filler particles can contribute to the total porosity of the paper‐derived sintering products, as well.…”
Section: Design and Manufacturing Of Highly Filled Papersmentioning
confidence: 99%
See 3 more Smart Citations